Impact of Climate Change on Coastal Agriculture - Geethalakshmi, V.; Manikandan, N.; Sumathi, S.; Bhuvaneswari, K.; Gowtham, R.; Pannerselvam, S. (International Journal of Economic Plants, 2016)
Climate change is recognized as a significant man-made global environmental challenge. It is also treated as a threat. Consequently, there is now a growing recognition of the vulnerability of key sectors of economy and development due to climate change. It is predicted that climate change could have devastating impacts on agriculture. The predicted sea-level rise will threaten valuable coastal agricultural land, particularly in low-lying areas. Biodiversity would be reduced in some of the most fragile environments, such as Sunderbans and tropical forests. Climate change imposes higher level of vulnerability mostly in crop agriculture sector and then fisheries, livestock and health respectively. Yield of most of the crops would be negatively impacted by rise in temperature and erratic rainfall, flooding, droughts, salinity, etc. As a consequence of climate change the trend shows that drier regions would be drier in the winter season. Therefore, possibility of growing rain fed crops would be diminished. During the dry months of March and April, salinity problems, resulting from seawater intrusion, are more acute and lands are commonly let fallow as crop productions restricted by the presence of salt. The Temperature Humidity Index (THI), an index used to define losses due to thermal stress is highest in the months of September–April and is likely to remain under highly stressful conditions in the 2030s. The livestock in the Coastal regions are likely to be highly vulnerable with consequent adverse impacts on its productivity throughout the year in the 2030 scenario with THI above 80.